2019
DOI: 10.11591/ijphs.v8i4.18348
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diabetes mellitus patient behavior questionnaire in primary health care service

Abstract: This study aimed to develop and validation a questionnaire as measurement instrument for knowledge and adherence behavior of DM patients in primary health care. Cross sectional study design was conducted in diabetes mellitus patient. Inclusion criteria were patients in the age group 18-65 years, diagnosed with DM, receiving at least one oral antidiabetic medication. Questionnaire questions for behavioral item were developed based on Diabetes Mellitus management guidelines and references to previous studies. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The questionnaire about the adherence to insulin used was adapted from the Morisky Medication Adherence Scale (MMAS) (MIAS) (Osborn & Gonzalez, 2016). There was a questionnaire about factors determining insulin adherence like diabetes knowledge, such as the patient diabetes knowledge questionnaire (PDKQ) and diabetes knowledge questionnaire (DKQ) in the Taiwanese population; a questionnaire about quality of life, such as the Asian diabetes quality of life questionnaire and Indonesian version of the A the audit of diabetes dependent quality of life questionnaire (ADDQoL); and the questionnaire about diabetes mellitus patient behaviour in primary health care service (Hsieh et al, 2022;Lim et al, 2023;Oliveira et al, 2022;Permana et al, 2021;Rooswita et al, 2021;Saputri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire about the adherence to insulin used was adapted from the Morisky Medication Adherence Scale (MMAS) (MIAS) (Osborn & Gonzalez, 2016). There was a questionnaire about factors determining insulin adherence like diabetes knowledge, such as the patient diabetes knowledge questionnaire (PDKQ) and diabetes knowledge questionnaire (DKQ) in the Taiwanese population; a questionnaire about quality of life, such as the Asian diabetes quality of life questionnaire and Indonesian version of the A the audit of diabetes dependent quality of life questionnaire (ADDQoL); and the questionnaire about diabetes mellitus patient behaviour in primary health care service (Hsieh et al, 2022;Lim et al, 2023;Oliveira et al, 2022;Permana et al, 2021;Rooswita et al, 2021;Saputri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Diabetes mellitus patients must receive education and counselling regarding treatment and lifestyle adjustment in order to reach the anticipated therapeutic aims. 7,8 Research has demonstrated that pharmacist counselling improves blood sugar control and overall quality of life in individuals with diabetes mellitus. [9][10][11][12][13] Pharmacy brief counselling is a newly created counselling technique.…”
mentioning
confidence: 99%